YOGA BHUWANA PRAWERTI SEBAGAI METODE DALAM MENINGKATKAN KESEHATAN ORGAN TUBUH - Ni Kadek Tuti Sri Devi (Widya Genitri : Jurnal Ilmiah Pendidikan, Agama dan Kebudayaan Hindu, 2021)
A healthy and fit body condition is one of the most important things in life. Various studies have shown that a healthy and fit body can be obtained through yoga activities. One type of yoga that provides health for the body's organs is Yoga Bhuwana Prawerti which is preserved at the Seruling Dewata Islamic Boarding School, Bantas Village, East Selemadeg District, Tabanan Regency, Bali Province. Bhuwana Prawerti Yoga has six movements consisting of Bhaumanasana, Bhumisayasana, Bhumipalasana, Bhumipadasana, Nagaparwatasana and Bhuwanadipasana. This yoga practice also has a different method by adding the number of repetitions at each stage. Starting from stage 1 with 5 repetitions to stage 9 with 21 repetitions. This is done to train discipline in doing something to get maximum results. The number 21 is also taken on the grounds that the cells in the human body will die and undergo rejuvenation once every 21 days.